2019
DOI: 10.15283/ijsc18094
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Role of Circulating Immune Cell Subtypes Early after Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Acute Leukemia

Abstract: Background and Objectives Cells of innate immunity normally recover in the first weeks to months after allogenenic hematopoietic stem cell transplantation (allo-HSCT). Their relevance in terms of graft-versus-host disease (GVHD) and graft-versus-leukemia (GVL) effect is largely unknown. The predictive role of early recovery in the immune cells on acute GVHD and GVL effect after allo-HSCT was investigated in patients with acute leukemia who achieved the first complete remission. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The benefit from NK cell may be attributed to its introduction of controllable GVHD together with an optimal degree of GVL effect, In a separate study, it was shown that serum IFN-γ increased along with the expansion of NKT-like cells in GVHD patients, and patients benefitted through treatment with basiliximab (anti-CD25 antibody) and etanercept (anti- IFN-γ antibody) [3]. Kim et al revealed that lower frequencies of iNKT cells (invariant NKT cells) were associated with higher GVHD incidence [19]. The study of NK cells showed similar suppression function on GVHD [20].…”
Section: Discussionmentioning
confidence: 99%
“…The benefit from NK cell may be attributed to its introduction of controllable GVHD together with an optimal degree of GVL effect, In a separate study, it was shown that serum IFN-γ increased along with the expansion of NKT-like cells in GVHD patients, and patients benefitted through treatment with basiliximab (anti-CD25 antibody) and etanercept (anti- IFN-γ antibody) [3]. Kim et al revealed that lower frequencies of iNKT cells (invariant NKT cells) were associated with higher GVHD incidence [19]. The study of NK cells showed similar suppression function on GVHD [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to MAIT cells, they are capable of secreting large amounts of cytokines upon activation in TCR-dependent and TCR-independent manners [89]. High numbers of iNKT cells in the graft and early after allo-HCT are associated with protection against GvHD [101][102][103][104][105][106] and relapse [103,106,107] and seems to be correlated with improved overall survival [103]. Therefore, using this T cell population as immunotherapy and increasing the iNKT cell numbers after allo-HCT has gained attention in recent years.…”
Section: Inkt Cellsmentioning
confidence: 99%
“…In humans, MDSCs have been related to worse outcomes in hematological malignancies (60,61); therefore, MDSCs were suspected to be involved in relapses after allo-HSCT. However, in the allo-HSCT setting, only a few prospective studies have reported a significantly higher probability of relapse in patients with higher M-MDSC frequencies than other patients, in the 30 days following allo-HSCT (52,53). Other studies suggested that MDSCs preserved the GVT effect (26,56).…”
Section: Impact Of Mdscs On the Gvt Effectmentioning
confidence: 99%